Challenges in Open Innovation A case study of Positive Footprint Housing - NILSSON, OLIVIA; ROYSON, LINA (My University, 2018)
In order to be able to meet the demands of a growing population, organizations must review their ways of working if they are to prevent increased climate change and the depletion of natural resources. Thus, to account for the need of sustainable development, organizations must foster innovative solutions and find new ways to operate. By using the approach of open innovation, and thereby go beyond the organization’s own boundaries, organizations can obtain external resources to stay competitive and innovative. This thesis aims to contribute to the literature on open innovation by investigating the approach in a new context - the Positive Footprint Housing context (PFH). PFH is a cross-sectional research platform between academia and industry, with the purpose to generate new and more sustainable ways of designing housing projects. The platform’s outputs are currently being realized in three housing projects, which thereby function as full-scale laboratories for implementing sustainable housing. In particular, the study aims at identifying and analyzing the challenges the PFH platform has encountered, from a management point of view. To be able to achieve the purpose of the study, an inductive and qualitative research strategy have been used, and data collection has been made through interviews, observations and documents. Furthermore, a literature review was undertaken in order to form a theoretical framework related to the research problem, which was used to support and enhance the analysis. The findings of the study show that the greatest challenges from a management point of view in the PFH platform are concerned with how to lead and organize a group with various actors involved, coming from widely spread organizations and having different goals and ways of working. Moreover, the literature shows that specific context characteristics have an impact on open innovation collaborations. In the construction industry, the high complexity as well as the high variety of actors, constitute as factors that bring difficulties for innovation in the industry. The analysis shows that the PFH platform have been a successful project in the sense that it has been a functional collaboration that have resulted in several sustainability-oriented solutions. Although it can be hard working with open innovation due to the variety of the actors involved, the PFH collaboration seems to have benefited the members of the group. It seems as there are some factors that function as enablers for the platform, namely innovation broker, management engagement, demonstration projects etc., which therefore could be considered to be critical for the future of the PFH platform. The findings of this thesis could contribute to the literature on open innovation by filling the gap of case studies on open innovation within the construction industry, in the context of sustainability, and thereby provide new insights of how innovative and sustainable solutions can be implemented in a construction project.
Keywords: Samhällsbyggnadsteknik; Civil Engineering